PERBEDAAN KINERJA MARKETING UMKM KONVENSIONAL DAN UMKM GO DIGITAL - Lucia Ika Fitriastuti; Yohannes Vemberi; Arief Dermawan; Saifudin Zuhri (Sekolah Tinggi Ilmu Ekonomi SBI, 2025)
MSMEs play a significant role in developing the national economy. The large number of MSMEs indicates that some still employ conventional marketing strategies, while others have gone digital. The purpose of this study is to quantitatively determine whether there are differences in marketing performance between conventional MSMEs and those that have gone digital, particularly in Daerah Istimewa Yogyakarta. This study utilized primary data obtained from a survey of 100 MSMEs in Daerah Istimewa Yogyakarta. The data analysis technique used was quantitative descriptive analysis with the nonparametric Mann-Whitney U test. The results indicate a difference in marketing performance between conventional MSMEs and those that have gone digital. This study recommends that conventional MSMEs employ alternative strategies to improve their marketing performance, such as developing digital marketing strategies or utilizing e-marketing.